Aspek Human Security dalam Pembatasan Masuknya Orang Asing ke Indonesia karena Pandemi Covid-19 - Junior Perdana Sande (Indonesian Perspective, 2021)
This article aims to analyze Indonesia’s Immigration policy in restricting the arrival of foreigners due to the Covid-19 pandemic. Through a qualitative research method and descriptive analysis approach, it can be explained how the concept of human security and state sovereignty affects the making and implementation of a series of policies to restrict the arrival of foreigners to Indonesia during the Covid-19 pandemic. The author seeks to provide an analysis of how the Covid-19 pandemic has become a real threat to global human security and how the Indonesian government seeks to protect the Indonesian people by limiting the arrival of foreigners to minimize the spread of Covid-19. The Indonesian government does not take a lockdown policy, but prefers policies that can protect health while protecting the economic activities of the Indonesian people. In the ‘New Normal’ way, Indonesia’s immigration policies continue to adapt to support economic recovery while supporting the implementation of health protocols.